The Effectiveness Of Using Kahoot Application As Media Of Vocabulary Mastery At Tenth Grade Of SMAN 1 Bukittinggi - Nurfajrina; Eliza (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2023)
The aim of this research was to know how the effectiveness of using Kahoot as media of vocabulary mastery at tenth grade of SMAN 1 Bukittinggi. The design of this research was descriptive quantitative research. The instrument of this research was documentation for collecting students vocabulary scores of the students after using Kahoot application. The population of this research was all students at tenth grade of SMAN 1 Bukittinggi which consists of 12 classes. The sample was 68 students which were taken from two classes by using purposive sampling technique. Based on the results of this research, it was concluded using Kahoot application as media of vocabulary mastery at tenth grade of SMAN 1 Bukittinggi was on good category where the students’ mean scores was 77,31 lies on the percentage 66-79 which was effective on rating quality. Furthermore, using Kahoot application was effective to be used as media of vocabulary mastery at tenth grade of Bukittinggi.